Pemanfaatan Lubang Biopori Sebagai Resapan Air Hujan dan Kompos Alami di Wilayah Kelurahan Pasuluhan Kecamatan Walantaka - Desty Endrawati Subroto; Halimi Rifa’ata Fauzan; Muhammad Fadel Hasan Maliki; Wina Mulyani (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to evaluate the effectiveness of using biopore holes in Pasuluhan Village as a means of absorbing rainwater and producing natural compost. To manage the intensity of rainwater entering the soil and processing organic waste, Pasuluhan residents can create biopore absorption holes as a simple technology that has great potential in managing the intensity of rainwater absorbing into the soil and managing organic waste. The method used includes making biopore holes in 6 strategic locations in the Pasuluhan area. Several points were used to make biopore holes, namely at the residences of Pak Sukriadi, Pak Subur and Pasuluhan Village. The research results show that biopore holes are able to increase the soil’s absorption capacity for rainwater, which has a positive impact in reducing waterlogging and flooding. Apart from that, biopore holes have also proven effective in processing organic waste into compost which is beneficial for soil fertility. Thus, it is hoped that the application of this technology can be a practical and environmentally friendly solution and can be easily applied by local residents in managing water and waste resources in the Pasuluhan area.